THE INFLUENCE OF SERVICE QUALITY ON COSTUMER SATISFACTION IN FINANCING PT.BANK SAHABAT SAMPOERNA BRANCH OFFICE PEKANBARU - Fakhri, Rizqi; Kurniawan, Teuku Reza (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This study was conducted to determine the effect of service quality on costumer satisfaction finance at PT.Bank Sahabat Sampoerna Branch Office Pekanbaru. The population in this study are all customer financing at PT.Bank Sahabat Sampoerna Branch Office Pekanbaru until in the end of December 2015 amounted to 997 People. Samples taken as many as as 91 people refer to the formula Slovin, data collection techniques in this study was a questionnaire and interview. Analysis of the data in this study using descriptive and quantitative analysis. Descriptive is a comparison between the actual reality with the theoris that had to do with problems in order to draw a conclusion and are tabuled in the form of tables of frequency distribution. While the quantitative methods of research based on the data that can be calculated to produce a solid assessment. Simple linear regression results in this study is Y = -1,735 + 0,331X. by using the t test, obtainet ttabel value of 19,636 and a mean value tcount 19,636>ttable 1,986, which means the quality of service have a significant effect on costumer satisfaction finance at PT.Bank Sahabat Sampoerna Branch Office Pekanbaru with great effect 81,20%